An empirical analysis of bill payment choices - Anneke Kosse (Bank of Canada, 2021)
The aim of this paper is to examine which payment instruments Canadians use for paying bills and to assess the factors driving their bill payment behaviour. I use 2019 survey data collected among over 4,000 Canadians and estimate a set of binomial and multinomial regressions to assess the factors influencing consumers' use and perception of different bill payment options. I find that there is no single dominant payment method for all consumer groups: demographics, financial situation, new technology adoption and POS payment habits play a significant role in the usage of bill payment methods as well as in consumers' stated reasons and barriers of use. Moreover, I demonstrate that consumers' bill payment behaviour strongly varies by bill type. The conclusions are useful for policy discussions on how to encourage a migration away from paper-based payment methods and how to (re)design a retail payments system to accommodate end-user needs.
Keywords: D1; D9; G2; 330; Bank notes; Econometric and statistical methods; Financial services; Payment clearingand settlement systems